2014
DOI: 10.3390/su6128720
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Power Generation Industry Efficiency Evaluation in China

Abstract: Abstract:In this paper, we compare the properties of the traditional additive-based data envelopment analysis (hereafter, referred to as DEA) models and propose two generalized DEA models, i.e., the big M additive-based DEA (hereafter, referred to as BMA) model and the big M additive-based super-efficiency DEA (hereafter, referred to as BMAS) model, to evaluate the performance of the biomass power plants in China in 2012. The virtues of the new models are two-fold: one is that they inherited the properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Great efforts have been made in China to reduce energy consumption [1], however, just as Lin et al stated in their paper, "China is a fast developing country with a vast size, and there are great differences in both the amount and structure of residential energy consumption at the provincial level" [12], therefore, they conducted a factor analysis and found that population, economic development level, energy resource endowment, and climatic conditions are the main factors driving residential energy consumption [12], their efforts could contribute to a deeper understanding on Chinese residents' energy consumption demands in the future. Another paper submitted by Yan and Tao [13] focuses on evaluating the performance of the biomass power plants in China in 2012, by developing and employing two new DEA (data envelopment analysis) models they found that there is a great technology gap between the biomass power plants in the northern part of China and those in the southern part of China. The results from these two papers show that, regardless of energy consumption or energy technologies [12,13], regional difference should be considered as a basic factor in sustainability policy-making.…”
Section: Contributionsmentioning
confidence: 99%
“…Great efforts have been made in China to reduce energy consumption [1], however, just as Lin et al stated in their paper, "China is a fast developing country with a vast size, and there are great differences in both the amount and structure of residential energy consumption at the provincial level" [12], therefore, they conducted a factor analysis and found that population, economic development level, energy resource endowment, and climatic conditions are the main factors driving residential energy consumption [12], their efforts could contribute to a deeper understanding on Chinese residents' energy consumption demands in the future. Another paper submitted by Yan and Tao [13] focuses on evaluating the performance of the biomass power plants in China in 2012, by developing and employing two new DEA (data envelopment analysis) models they found that there is a great technology gap between the biomass power plants in the northern part of China and those in the southern part of China. The results from these two papers show that, regardless of energy consumption or energy technologies [12,13], regional difference should be considered as a basic factor in sustainability policy-making.…”
Section: Contributionsmentioning
confidence: 99%
“…Another paper submitted by Yan and Tao [13] focuses on evaluating the performance of the biomass power plants in China in 2012, by developing and employing two new DEA (data envelopment analysis) models they found that there is a great technology gap between the biomass power plants in the northern part of China and those in the southern part of China. The results from these two papers show that, regardless of energy consumption or energy technologies [12,13], regional difference should be considered as a basic factor in sustainability policy-making.…”
Section: Contributionsmentioning
confidence: 99%
“…Biomass-based generation is deemed as a promising utilization pathway of renewable energy in China because of its carbon neutrality feature [4], resource abundance [5,6] and its stability compared to other renewable power options, such as wind and solar [7]. Since China's Renewable Energy Law was promulgated in 2006, the biomass-based generation industry has entered a new stage of rapid expansion.…”
Section: Introductionmentioning
confidence: 99%